Bibliometric Analysis: The Concept of Fair Trade In International Trade - Anggara, Reksi; Sulaksono, Tunjung; Suranto (Jurnal Bisnis dan Keuangan, 2024)
This study aims to map global scientific publications with the topic of fair trade in international trade to get trends and issues that can be further researched related to the topic. The method used in this study is a qualitative method with a literature study approach using bibliometric analysis. The data used is 54 articles indexed by Scopus in the last ten years. VOSviewer is used to provide a visual examination of the occurrence of keywords. The findings in this study show that publications with the theme of fair trade in international trade have decreased over the past ten years. In 2013 became the most research publications, the United States became the country that contributed the most to the publication of this research. Then, Ulgiati, S. is the author who contributed significantly to this scientific research. Other findings from this study have also shown that the field of study of Social Sciences is the highest, with a total percentage of 34%. Beijing Normal University and the Parthenope University of Naples as contributing institutions in publications on this theme. The research also shows that the most researched topics are dominant issues such as sustainable development goals, consumer behavior in developing countries, and world food trade.